MANGROVE PLANTING AND EARTHQUAKE EDUCATION AS NATURAL DISASTER MITIGATION EFFORTS - Nur Hidayati; Karsim; Alfinaul Firdaus; Sri Aninda Heptya Lutfihani; Nilam Fatmawati (Journal of Community Research and Engagement, 2025)
Background: Java Island is a highly disaster-prone area in Indonesia due to its location in the convergence zone, where two tectonic plates meet. Mangrove planting and earthquake education are two natural disaster mitigation efforts that complement each other in reducing the risk and impact of disasters, especially in coastal areas that are vulnerable to earthquakes and tsunamis. Objectives: The purpose of this activity is to increase community knowledge by educating about natural disaster mitigation and earthquakes, as well as preventing sea abrasion disasters through mangrove planting. Method: The method of implementing community service activities includes education with lecture methods and mangrove planting. The activity was attended by approximately 28 people in Klayar Hamlet, Sidokelar Village, Paciran Subdistrict, Lamongan, East Java. Results: The post-test results showed an increase in knowledge about earthquake disaster mitigation. Mangrove planting activities totaling 110 trees ran smoothly. Evaluation and follow-up are carried out with a questionnaire while tree planting is evaluated once a year to see the results. Conclusion: Mangrove planting activities totaling 110 trees ran smoothly. Evaluation and follow-up are carried out with a questionnaire while tree planting is evaluated once a year to see the results.